Initial protocol for a national evaluation of an area-based intervention programme (A Better Start) on early-life outcomes: a longitudinal cohort study with comparison (control) cohort samples. Issue 8 (28th August 2017) - Barlow, Jane; Beake, Sarah; Bick, Debra; Bryson, Caroline; Day, Laurie; Gilby, Nicholas; Glover, Vivette; Knibbs, Sarah; Leyland, Alastair; Lindsay, Geoff; Mathers, Sandra; McKenna, Katharine; et al.
Abstract : Introduction: Pregnancy and the first few years of a child's life are important windows of opportunity in which to equalise life chances. A Better Start (ABS) is an area-based intervention being delivered in five areas of socioeconomic disadvantage across England. This protocol describes an evaluation of the impact and cost-effectiveness of ABS. Methods and analysis: The evaluation of ABS comprises a mixed-methods design including impact, cost-effectiveness and process components. It involves a cohort study in the 5 ABS areas and 15 matched comparison sites (n=2885), beginning in pregnancy in 2017 and ending in 2024 when the child is age 7, with a separate cross-sectional baseline survey in 2016/2017. Process data will include a profiling of the structure and services being provided in the five ABS sites at baseline and yearly thereafter, and data regarding the participating families and the services that they receive. Eligible participants will include pregnant women living within the designated sites, with recruitment beginning at 16 weeks of pregnancy. Data collection will involve interviewer-administered and self-completion surveys at eight time points. Primary outcomes include nutrition, socioemotional development, speech, language and learning. Data analysis will include the use of propensity score techniques to construct matched programme and comparison groups, and a range of statistical techniques to calculate the difference in differences between the intervention and comparison groups. The economic evaluation will involve a within-cohort study economic evaluation to compare individual-level costs and outcomes, and a decision analytic cost-effectiveness model to estimate the expected incremental cost per unit change in primary outcomes for ABS in comparison to usual care. Ethics and dissemination: Ethical approval to conduct the study has been obtained. The learning and dissemination workstream involves working within and across the sites to generate learning via communities of practice and a range of learning and dissemination events.